Taxonomy and distribution of Seaweeds in selected sites in Panabolon Island, Nueva Valencia, Guimaras. - Monte, Vincent Troy G. (1999.)
The species composition and distribution of seaweeds in 3 intertidal stations in the North-facing side of Panabolon island, Nueva Valencia, Guimaras was investigated in February, 1999. Stratified sampling of the seaweed community from nearest the shore where seaweed growth began up to 50 meters seaward was carried out. All seaweeds found inside quadrants (0.5m X 0.5m) laid out following the modified belt transect method were noted and identified. Frequency and cover were computed by taxa (either by class or by species) and compared among species and among stations. Also, indices of diversity and similarity were computed, then comparisons in seaweed assemblage among stations were made., A total of 22 species in 15 genera belonging to 9 orders in 3 major classes of seaweeds were seen in this side of the island. The Class Chlorophyceae (green seaweeds) comprised more than 50 of the total species recorded in the area. The green seaweeds also dominated in frequency of occurrence (84-95) and in cover 78-95). Halimedea, represented by 4 species, was found to be the most important genus. The distribution of seaweeds, the dominance of the green seaweeds and of the genus Halimeda, were discussed in relation to dept and substrate characteristics.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Seaweeds -- Valencia, Guimaras